Use of Xpert MTB/RIF for diagnosis of pediatric tuberculosis in Indonesia - Rina Triasih; Amalia Setyati; Dwikisworo Setyowireni; Titik Nuryastuti; Rachma Dewi Isnaini Putri; Emi Rusdiyati (Indonesian Pediatric Society, 2020)
Background The Xpert MTB/RIF assay demonstrated a better diagnostic value than sputum smear for TB in adults and children. Objective To evaluate the use of Xpert MTB/RIF for TB diagnosis in children. Methods We conducted a prospective study in Yogyakarta, Indonesia, involving 19 primary health centers (PHCs) and one provincial hospital. Children aged 0-14 years with suspected TB who visited the study sites were screened. Subjects underwent history-taking, physical examination, tuberculin skin test, chest X-ray, as well as sputum induction for Xpert MTB/RIF assay, sputum smear, and TB culture. The diagnosis of TB was made by doctors based on the results of investigations, as follows: certain TB (bacteriological confirmation), probable TB, and possible TB. Results Of 80 subjects, 21 (26%) were diagnosed with TB disease (4 certain TB and 17 probable TB). Sputum induction was successfully performed in 79 children. None of the children had positive sputum smears. Mycobacterium tuberculosis was detected by Xpert MTB/RIF in 4 children, accounting for 5% of all children with suspected TB, or 19% among children with TB disease. The 4 Xpert MTB/RIF-positive subjects had severe TB disease and were rifampicin-sensitive. Conclusion Xpert MTB/RIF may improve case finding among children with severe TB disease with negative sputum smear.